Neurogenesis as a Tool for Spinal Cord Injury - Havelikova, Katerina; Smejkalova, Barbora; Jendelova, Pavla (International journal of molecular sciences, 2022)
Spinal cord injury is a devastating medical condition with no effective treatment. One approach to SCI treatment may be provided by stem cells (SCs). Studies have mainly focused on the transplantation of exogenous SCs, but the induction of endogenous SCs has also been considered as an alternative. While the differentiation potential of neural stem cells in the brain neurogenic regions has been known for decades, there are ongoing debates regarding the multipotent differentiation potential of the ependymal cells of the central canal in the spinal cord (SCECs). Following spinal cord insult, SCECs start to proliferate and differentiate mostly into astrocytes and partly into oligodendrocytes, but not into neurons. However, there are several approaches concerning how to increase neurogenesis in the injured spinal cord, which are discussed in this review. The potential treatment approaches include drug administration, the reduction of neuroinflammation, neuromodulation with physical factors and in vivo reprogramming.
Keywords: Spinal Cord; Neurons; neurogeneze; poranění míchy; buněčná diferenciace; Cell Differentiation; Humans; Neural Stem Cells; Neurogenesis; Spinal Cord Injuries; mícha; neurony; lidé; nervové kmenové buňky